The effect of ischemic preconditioning on the cardiac autonomic nervous system after exercise: A systematic review and meta-analysis: Ischemic preconditioning affects the cardiac autonomic nervous system - Wang, Chuan qiu shui; Wang, Kun; Liu, Hengxu; Liu, Shi qi; Yang, Yi; Luo, Jiong (Quality in Sport, 2024)
Aims: The objective of this study is to comprehensively evaluate the influence of ischemic preconditioning intervention on the autonomic control nerves of athletes during the post-exercise period. Methods: Randomized controlled trials (RCTs) were sourced from PubMed, Web of Science, Embase, Wipo, CNKI, and Cochrane databases, covering the period from inception to December 2023. The quality of the included RCTs was evaluated using the Cochrane Risk Assessment Tool, and a systematic assessment was conducted using RevMan 5.3. Results: Seven randomized controlled trials (RCTs) involving 88 subjects were included in the analysis. The meta-analysis indicated that ischemic preconditioning significantly improved heart rate during both short-term recoveries (mean difference [MD] = -3.99, 95% confidence interval [CI]: -5.93 to -2.05, p < 0.00001) and long-term recovery post-exercise (MD = -9.73, 95% CI: -12.74 to -6.73, p < 0.00001). However, there was no significant effect observed on resting state heart rate variability (HRV) or peak heart rate (HR peak) at the end of exercise (MD = -0.16, 95% CI: -2.46 to 2.14, p = 0.89). Conclusion: Ischemic preconditioning facilitates the prompt reactivation of cardiac parasympathetic nerves following exercise and enhances both short-term and long-term heart rate recovery. The extent of this recovery effect may be influenced by factors such as the dosage of the intervention, the individual’s training level, and the intensity of the exercise performed. Limitation: Given the limited number of included studies, the small sample size, and the unclear definition of some experimental procedures, it is essential to design more rigorous and comprehensive high-quality randomized controlled trials (RCTs) in the future to investigate the effects of ischemic preconditioning on cardiac autonomic control nerves following exercise. Registration: INPLASY202440069